Outcomes of Inpatient Rehabilitation in Patients With Simultaneous Bilateral Total Knee Arthroplasty. Issue 8 (18th November 2015) - Chu, Samuel K.; Babu, Ashwin N.; McCormick, Zachary; Mathews, Amy; Toledo, Santiago; Oswald, Matthew
Abstract: Background: The number of total knee arthroplasty (TKA) procedures performed in the United States is increasing each year, and the number of bilateral TKA procedures has also increased during the past 2 decades. However, few studies in the literature have investigated the rehabilitation outcomes of patients who undergo bilateral TKA. This study was performed to provide information on the benefits and role of inpatient rehabilitation for patients after bilateral TKA. Objective: To investigate the functional outcomes, complications, and transfer rates of patients in the inpatient rehabilitation setting who undergo simultaneous bilateral TKA. Design: Retrospective cohort study. Setting: Freestanding inpatient rehabilitation hospital. Patients: Ninety‐four patients admitted to an inpatient rehabilitation hospital after simultaneous bilateral TKA from 2008‐2013. Methods: Retrospective chart review of demographic, clinical, and functional data for patients admitted to inpatient rehabilitation after simultaneous bilateral TKA. Main Outcome Measures: Length of stay, admission and discharge Functional Independence Measure (FIM), and FIM efficiency. Results: The study included 27 male (28.7%) and 67 female (71.3%) patients aged 42.0‐86.9 years, with a mean of 65.6 ± 10.2 years. Mean length of time between surgery and admission to inpatient rehabilitation was 4.5 ± 3.3 days. Mean length of stay in rehabilitation was 11.7 ± 4.2 days. Mean admission and discharge FIM scores were 87.3 ± 11.7 and 113.4 ± 4.8, respectively, with a mean FIM gain of 26.1 ± 10.5. The mean FIM efficiency was 2.33 ± 0.84. Eight patients required transfer to an acute care hospital. Complications leading to transfer to acute care facilities included sepsis, cardiac arrhythmias, knee dislocation, and suspected small bowel obstruction. Eighty‐eight patients were discharged home, 4 patients were discharged to skilled nursing facilities, and 2 patients were transferred to an acute care hospital and did not return to the inpatient rehabilitation hospital. Conclusions: After undergoing simultaneous bilateral TKA, patients demonstrate functional gains when admitted to inpatient rehabilitation facilities based on FIM gains and FIM efficiency scores; 8.5% of patients in this cohort required transfer to an acute care facility as a result of complications during inpatient rehabilitation, and 93.6% of patients were discharged home.